2024
DOI: 10.3390/su16020646
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Water Quality Monitoring: Using Satellite Images for Temporal and Spatial Monitoring of Thermal Pollution in Water Resources

Reza Naimaee,
Abbas Kiani,
Sina Jarahizadeh
et al.

Abstract: Thermal pollution reduces water quality through any process that leads to a change in the water’s ambient temperature. Karun is one of the most relevant sources of water supply in Iran, and its pollution, created by industrial, urban, and agricultural issues, has been one of the most critical challenges throughout the last few years. As the water temperature rises, the amount of dissolved oxygen in it decreases, thereby affecting the entire ecosystem associated with it. Drainage of urban and industrial runoff … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Additionally, obtaining field measurements is often time-consuming, expensive, and limited by spatial and temporal constraints, thereby hindering effective water quality management and improvement efforts [21]. To address these challenges, utilizing satellite remote sensing to monitor river water quality is an economical, efficient, and large-scale approach to monitoring water bodies [22]. In light of these challenges, quantitative remote sensing research to evaluate the TLI of rivers holds substantial practical value [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, obtaining field measurements is often time-consuming, expensive, and limited by spatial and temporal constraints, thereby hindering effective water quality management and improvement efforts [21]. To address these challenges, utilizing satellite remote sensing to monitor river water quality is an economical, efficient, and large-scale approach to monitoring water bodies [22]. In light of these challenges, quantitative remote sensing research to evaluate the TLI of rivers holds substantial practical value [15].…”
Section: Introductionmentioning
confidence: 99%
“…In light of these challenges, quantitative remote sensing research to evaluate the TLI of rivers holds substantial practical value [15]. Research has demonstrated that combining remote sensing monitoring with conventional ground-based monitoring techniques can offer a more comprehensive view of water environmental conditions, crucial for effective watershed management [22][23][24]. This integrated approach enables more effective monitoring of the trophic level of water bodies, with remote sensing serving acting as a vital supplement to the design and enhancement of ground-based monitoring systems [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the monitoring of water bodies and the subsequent assessment of possible risks rises in importance. This problem is being solved and, simultaneously, the need of using new and economically more effective monitoring methods used to check the decrease of polluting sources is emphasized [30]. A major segment is the sustainability of aquatic ecosystems, where tools, indicators, and approaches currently used in the field of aquatic ecosystems and their potential contamination play an important role [31].…”
mentioning
confidence: 99%